Infiltration Characteristics of Some Hill Soils of Lower Dhauladhar Ranges of Himachal Pradesh - Bhagat, R. M. (Indian Forester, 1987)
Based on basic field infiltration equations, five Dhauladhar range forest hill soils were studied. Experimentally derived parameters indicated entry of water into soil to increase in a coarse textured, less compact soil. whereas the infiltration is just the reverse in relatively fine textured, compact soils. The structural index of these soils was in conformity with the hydraulic parameters studied.